PENGARUH MODIFIKASI HMT (HEAT MOISTURE TREATMENT) TERHADAP SIFAT FISIKOKIMIA DAN NILAI ORGANOLEPTIK TEPUNG SAGU (Metroxylon sp) - Fajri, Ferawati (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2016)
The research objective was to determine the effect of heat moisture treatment (HMT) of sago flour on the physicochemical and sensory properties of the product. The research was conducted at the Laboratory of Food Technology, Department of Food Science and Technology, Faculty of Technology and Agricultural Industry, Halu Oleo University. This study used a randomized complete block design, which consisting of four treatments with four replications. The treatments used were: R1 (HMT at 90oC), R2 (HMT at 100oC)), R3 (HMT at 110oC), and R4 (HMT at 120oC). The results showed that there was a significant influence of the HMT on the sensory and physicochemical characteristics of sago flour. There were highly significant effects of the HMT on such sensory properties as colour, aroma, texture, and flavor; but there was no significant effect on water content and ash content. HMT modifications of the sago starch was best performed in the treatment of R3 (HMT at 110oC). Keyword: sago flour starch modified, modification heat moisture treatment.